High Exposure to Livestock Pathogens in Southern Pudu (Pudu Puda) from Chile - Moreira-Arce, D (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
A significant gap in exposure data for most livestock and zoonotic pathogens is common for several Latin America deer species. This study examined the seroprevalence against 13 pathogens in 164 wild and captive southern pudu from Chile between 2011 and 2023. Livestock and zoonotic pathogen antibodies were detected in 22 of 109 wild pudus (20.18%; 95% CI: 13.34–29.18) and 17 of 55 captive pudus (30.91%; 95% CI: 19.52–44.96), including five Leptospira interrogans serovars (15.38% and 10.71%), Toxoplasma gondii (8.57% and 37.50%), Chlamydia abortus (3.03% and 12.82%), Neospora caninum (0.00% and 9.52%), and Pestivirus (8.00% and 6.67%). Risk factors were detected for Leptospira spp., showing that fawn pudu have statistically significantly higher risk of positivity than adults. In the case of T. gondii, pudu living in “free-range” have a lower risk of being positive for this parasite. In under-human-care pudu, a Pestivirus outbreak is the most strongly suspected as the cause of abortions in a zoo in the past. This study presents the first evidence of Chlamydia abortus in wildlife in South America and exposure to T. gondii, L. interrogans, and N. caninum in wild ungulate species in Chile. High seroprevalence of livestock pathogens such as Pestivirus and Leptospira Hardjo in wild animals suggests a livestock transmission in Chilean template forest. © 2024 by the authors.